Analisis Studi Kelayakan Pengembangan Bisnis dalam Keputusan Ekspansi: (Studi Kasus Batik Lochatara Kediri) - Agustin, Riska; Aini, Saqofa Nabilah; Romaisyah, Luqita; Lestari, Sekar Rizky Margi (Politeknik Negeri Ambon, 2024)
MSMEs which are growing rapidly in Indonesia play a role in economic growth and job creation, one of the sectors is the batik craft industry. In Kediri Regency, Lochatara Batik is a growing MSME and plans to expand its products and market share. Before carrying out expansion, it is necessary to carry out a business feasibility study analysis to find out whether the expansion plan is feasible or not. This research aims to analyze aspects in the Lochatara Batik business feasibility study related to the expansion plans that will be carried out. A descriptive qualitative method using observation, interviews and documentation of the owners and employees of Batik Lochatara was carried out in this research method. The results, according to legal aspects, market and marketing aspects, financial aspects, technical or operational aspects, management and organizational aspects, economic and social aspects as well as environmental impact aspects, the business and expansion planned by Batik Lochatara were declared feasible to carry out. The results of this analysis can also be used as a reference for company owners to identify and minimize obstacles and risks that arise in the business in the future.